Assessing and preventing low back pain in nurses. Implications for practice management - Gabriele, d’Ettorre (Acta Biomed, 2019)
BACKGROUND AND AIMS: The prevention of low back pain (LBP) among nurses employed in hospital departments represents a special concern for healthcare organizations globally. A growing literature evidences the need of workplace policy development related to organizational issues as strategic contribution to minimize the occurrence of LBP in healthcare sector. The purposes of this study were: 1) to analyze the relationship between shiftwork and acute LBP among female shift nurses; 2) to detect preventive interventions targeted on organizational issues. METHODS: The authors conducted a cross-sectional nested case-control analysis of data concerning acute LBP and staffing data for 671 nurses employed in the Departments of General Practice and Elderly Care Medicine. The statistical analysis consisted of a logistic regression to calculate incidence odds ratios with 95% confidence intervals. Chi-square test and t-test were used to examine the relationship between categorical and continuous data, respectively. RESULTS: The occurrence of acute LBP resulted significantly related to nightshift, extended shifts, obesity; the adoption of forward rotating schedules was found a protective factor in moderating the occupational risk of acute LBP in shift nurses. CONCLUSIONS: In this study the authors observed an association between shiftwork and acute LBP; improvement interventions should be aimed at: 1) moderating organizational risks linked with shiftwork schedules; 2) promoting healthy lifestyles. These interventions are suggested as a strategic way to effectively manage the phenomenon among female rotating shift nurses. (www.actabiomedica.it)